CASE OF A PATIENT WITH POSTPARTUM ECLAMPSIA - Aleksandar Nakov; Petko Isjanovski; Ana Kocevska; Nurdzan AJeti; Shqipe Sarachini - Hajdari (Македонско лекарско друштво = Macedonian medical association, 2025)
Gestational hypertension is hypertension without proteinuria or other signs/symptoms of preeclampsia that develops after 20 weeks of gestation in a patient with a previously normal blood pressure. Development of proteinuria upgrades the diagnosis to preeclampsia. Even without proteinuria, patients who develop severe hypertension or other features of severe disease are managed in the same way as those with preeclampsia with severe features.
Keywords: gestational hypertension; preeclampsia; eclampsia; convulsions